2019
DOI: 10.1002/ps.5361
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to nymphs and adults of Mahanarva spectabilis (Hemiptera: Cercopidae) by forage plants in fertilized soils

Abstract: BACKGROUND: Several factors may degrade pastures, in particular, inadequate nutrient application and spittlebug attacks. Mahanarva spectabilis (Distant, 1909) (Hemiptera: Cercopidae), one of the species that occur in Brazil, is a limiting pest in forage production. This study analyzes the influence of fertilization with the macronutrients nitrogen, phosphorus and potassium (NPK) on the survival of M. spectabilis nymphs, and the effects of damage by nymphs and adults on the production, quality and regrowth capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
(39 reference statements)
0
8
3
Order By: Relevance
“…S4c). This seems inconsistent with previous findings that plants compensate or tolerate herbivory more when growing in high nutrient conditions [31,32,[48][49][50][51]. However, it should be noted that in our experiment, the herbivores could choose between the plants.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…S4c). This seems inconsistent with previous findings that plants compensate or tolerate herbivory more when growing in high nutrient conditions [31,32,[48][49][50][51]. However, it should be noted that in our experiment, the herbivores could choose between the plants.…”
Section: Discussioncontrasting
confidence: 99%
“…S4c). This seems inconsistent with previous findings that plants compensate or tolerate herbivory more when growing in high nutrient conditions (Meyer 2000, Hawkes and Sullivan 2001, Alvarenga et al 2019, Garcia and Eubanks 2019, Getman-Pickering et al 2021, Zhong et al 2021). However, it should be noted that in our experiment, the herbivores could choose between the plants.…”
Section: Discussioncontrasting
confidence: 87%
“…According to Valério (2009), the spittlebug attack contributes to pasture degradation impacting the nutritional status of the plant and the potential of regrowth at different harvest management. It has been reported that wellestablished and fertilized pastures managed under proper management conditions, show greater tolerance to attack by Mahanarva spectabilis (Distant) (Alvarenga et al, 2019).…”
Section: Pestsmentioning
confidence: 99%
“…Spittlebug management strategies must be used together so that the control of this pest is sustainable and efficient. Among the management strategies used in Brazil, we highlight the diversification of pastures [13], chemical control [14], biological control [15,16], and the use of resistant plants [17]. The use of insecticides and botanical repellents is a widespread strategy, and studies of this nature are necessary for the management of forage pests.…”
Section: Introductionmentioning
confidence: 99%